Accessibility and use of food as determinant of the nutritional status of the population of the district Churubamba – Huánuco 2008 - Ríos Rojas, Maura (2009)
The aim of the research work was to determine the capacity of access and use of food and at the same time evaluate the nutritional status of the population; the study was developed with a sample shaped by 58 families of the rural areas of Macuay, Cascay and Pacapucro; in the district of Churubamba. The results demonstrate that the food access toward the different homes is in its majority of the agricultural activities, existing also the consumption of food processed as rice, sugar, noodles, oil and salt (19%). With respect to the frequency of food consumption, it was observed that the foods like potatoes (93,1) % sugar, (100%), rice (51.7%) oats (41%), oil (100%) and corn (34.4%), they consumed every day; fresh milk (41%) egg (48%) chicken (50%); few vegetables, twice per week; meat of cattle every month, hen, and cuy. Analyzing that the biggest consumption of food is based on carbohydrates and fats, being deficient in proteins, vitamins and minerals; what they demonstrate a deficit of balanced feeding. According on the assessment of the nutritional status of the sample in study, it was observed that students of 6 to 10 years old presented the greater index of malnutrition with a 39.5% of chronic malnutrition and a 34.9% of acute malnutrition; likewise, in children under 5 years old 41.7% presented chronic malnutrition and a 33.5% is with acute malnutrition. The access and the food use is deficient what determines the nutritional status of the population being the most affected the infantile and school population.